Interplay of anxiety, depression, vascular function, and biomarkers in post-myocardial infarction patients - Kafol, Jan; Jug, Borut; Božič Mijovski, Mojca; Tršan, Jure; Košuta, Daniel; Novaković, Marko (Frontiers in Physiology, 2025)
Background and aimsCoronary artery disease (CAD) is a leading cause of mortality. Depression and anxiety are common in CAD patients and negatively affect quality of life, physical functioning, and adherence to cardiac rehabilitation (CR) programs. This study aimed to identify possible associations with clinically relevant parameters, vascular function and blood biomarkers.MethodsParticipants were consecutively recruited during cardiac rehabilitation intake visits at the University Medical Centre Ljubljana within 4 months of myocardial infarction (MI). Hospital Anxiety and Depression Scale (HADS) scores were analyzed in relation to endothelial function (assessed with flow-mediated dilation), arterial stiffness, and blood biomarkers (fibrinogen, endocan, and brain-derived neurotrophic factor [BDNF]) in post-MI patients. All vascular and biomarker assessments were performed within 5 days of questionnaire completion and prior to the start of rehabilitation.ResultsThere were 105 patients included in the study. The median age was 56 years (49–62), and 80.0% of participants were male. Clinically relevant anxiety and depression were present in 29.5% and 21.9% of participants, respectively. Anxiety was significantly associated with younger age, higher body mass index, and increased arterial stiffness, with total HADS scores negatively correlated with age. Endothelial function showed no significant associations with HADS scores. Vital signs showed no significant differences, except for slightly higher systolic blood pressure in those with clinically relevant depression. Fibrinogen levels were significantly higher in participants with anxiety and depression, while endocan and BDNF levels were lower in those with anxiety.ConclusionDepression and especially anxiety are significantly associated with endothelial function and relevant biomarkers in post-MI patients. However, as HADS is a screening tool and not a diagnostic instrument, and given the study’s observational design, findings reflect associations rather than causality. Routine screening and targeted mental health support within CR programs might improve participation, enhance cardiovascular recovery, and optimize long-term outcomes. These findings underscore the clinical importance of psychological assessment in the early post-MI period and support the integration of mental health evaluation into cardiovascular care.